The frequency-following response : a window into human communication - Kraus, Nina; Anderson, Samira; White-Schwoch, Travis; Fay, Richard R.; Popper, Arthur N. (Springer handbook of auditory research, 2017)
This volume will cover a variety of topics, including child language development; hearing loss; listening in noise; statistical learning; poverty; auditory processing disorder; cochlear neuropathy; attention; and aging. It will appeal broadly to auditory scientists and in fact, any scientist interested in the biology of human communication and learning. The range of the book highlights the interdisciplinary series of questions that are pursued using the auditory frequency-following response and will accordingly attract a wide and diverse readership, while remaining a lasting resource for the field.